Providing health care interpreting in the Department of Radiation Oncology, Charlotte Maxeke Johannesburg Academic Hospital - Ndachi, Mbwéli (My University, 2014)
South African public hospitals face communication barriers between medical staff (more specifically doctors) and patients as a result of cultural and linguistic diversity. Consequently, medical staff and patients experience frustrations, errors in diagnosis have been recorded and multiple tests need to be run to determine patients’ conditions, all these at the expense of patients. The services of ad hoc untrained interpreters such as relatives (including children), other medical staff (including fellow doctors, nurses, cleaners and porters), and other patients are used to bridge communication barriers, since there is no statutory interpreting service. However, the use of ad hoc untrained interpreters has been shown to lead to more complications, including breach of patient confidentiality, distortion and/or omission of information, and patients turning to sangomas (traditional witchdoctors), only to return to the hospital when their conditions have worsened. In the first part of this study, conducted at the Department of Radiation Oncology, Charlotte Maxeke Johannesburg Academic Hospital in Johannesburg, semi-structured interviews were conducted with patients and medical staff members in order to obtain a clear picture of their linguistic profiles. Thereafter, in order to determine whether ad hoc interpreters such as nurses interpret better than trained interpreters, the interpreting performance of a professionally trained interpreter is contrasted with that of an ad hoc nurse interpreter, both interpreting in an oncology setting; and a thorough analysis of both performances is provided through the use of Conversation Analysis (CA). The present research report is therefore a first attempt to determine possible solutions to miscommunication in the South African health care setting in general and an oncology setting in particular, from the perspective of Interpreting Studies.